The impact of cavaletti height on dogs’ walking speed and its implications for ground reaction forces - Blake, Cara A.; Looney, Andrea L.; Merrill, Tracie D. (Frontiers in Veterinary Science, 2024)
The objective of this study was to investigate the effects of cavaletti pole height on temporospatial (TPS) and ground reaction force (GRF) variables as compared to a walking gait in healthy dogs.Procedures: This study utilized client-owned dogs to explore the effects of cavaletti pole height on TPS and GRF variables. Dogs were first walked over a validated pressure sensitive walkway (PSW) and then walked over the PSW over which six cavaletti poles were set. Cavaletti pole height was initially set at 2-inches and then increased incrementally to 4-inches, 6-inches and 8-inches. TPS and GRF variables were obtained for all dogs walking across a PSW without cavalettis and at each cavaletti height. TPS variables were then compared to those obtained at a normal walking gait. Results: Increasing cavaletti height resulted in significant decreases in walking gait velocity and the number of gait cycles per minute. Conversely, significant increases in gait cycle duration (duration of one complete cycle of gait, which includes the time from the initial contact of one paw to the subsequent contact of the same paw) and gait time (duration to walk the total distance on the PSW). were noted. Increases in stance time, normalized maximum force and normalized vertical impulse were observed. Conclusions and clinical relevance: Cavaletti height does influence TPS variables in in healthy dogs at a walking gait. The effects were most notable with regards to velocity. Due to the lack of consistent velocity for all cavaletti heights, no conclusions can be made regarding the effect of cavaletti height on ground reaction forces. Further investigation is needed to elucidate whether it is the velocity, cavaletti height or the combination, that impacts ground reaction force variables. When selecting cavaletti pole heights for a therapeutic exercise program, an increase in cavaletti height results in a slower walking gait.